Livros de compromisso: práticas em torno de um fazer livresco nas Minas setecentistas - Montanheiro, Fábio César [UNESP] (2007)
Taking as a starting point the idea that Discourse and History maintains inseparable bonds and that, through textual figurations of genres (Bakhtin, 1999) constituted in certain times and places the human being represents its relation with the lived one - concrete or imaginary - It is proposed in the present work the diplomatic edition and the analysis of three manuscript books produced by brotherhoods linked to the Parish of Our Lady of the Pillar of Vila Rica do Ouro Preto, in the Minas Gerais of the XVIII century. These are books designated as Livros de Compromisso. This kind of book is intended to govern the lay religious brotherhoods devoted to the worship of a saint or invocation of the Catholic Church; They function as their rules. The most common devotions in the first half of the Seventies in Minas were that of Our Lady of Rosario, mainly among blacks; and those of the Blessed Sacrament and St. Michael the Archangel, among the white people, especially the well-to-do, of the local elite (Boschi, 1986). This was the first reason for selecting the Livros de Compromisso from these three Brotherhoods. The second motif concerns the artistic character of the three Books, since all are very careful with questions of aesthetic order: they are enlightened, they present chapters beginning with capital letters and a careful calligraphy. In order to delimit and circumscribe the Livros de Compromisso approach, works from three areas of knowledge were used: Cultural History and New History, Philology and Discourse Analysis. The New History and Cultural History is a line of historiographical making that allows, among other aspects, the study of the forms of appropriation of cultural goods and in this line were important...